2019
DOI: 10.1038/s41598-019-49270-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase-change like process through bond switching in distorted and resonantly bonded crystal

Abstract: Although some methods to improve phase-change memory efficiency have been proposed, an effective experimental approach to induce a phase-change like process without external heat energy has not yet been reported. Herein we have shown that GeTe is a prototype phase-change material, which can exhibit a non-thermal phase-change-like process under uniaxial stress. Due to its structural characteristics like directional structural instability and resonance bonding under 1% uniaxial stress, we observed that bond swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
1
1
Order By: Relevance
“…Despite the demonstration of mobility values as low as 10 −4 cm 2 V −1 s −1 from the strained flexible devices fabricated from DPP-diEt, it is important to note that these measurements have been reliable over a number of devices (at least 3 devices) and such values of low mobility are not uncommon in solution processed organic semiconductors. 41,43 Although it has been observed that the single crystals of DPP-diMe can withstand strains up to 3–6%, we still observed a decrease in μ FET , for much lower strains in the device (strain range: 0.7–1.25%). This behaviour can be attributed to several factors such as the difference in strain between the layers involved in device fabrication, development of micro-cracks in the dielectric layer and the metal contacts with the crystal.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…Despite the demonstration of mobility values as low as 10 −4 cm 2 V −1 s −1 from the strained flexible devices fabricated from DPP-diEt, it is important to note that these measurements have been reliable over a number of devices (at least 3 devices) and such values of low mobility are not uncommon in solution processed organic semiconductors. 41,43 Although it has been observed that the single crystals of DPP-diMe can withstand strains up to 3–6%, we still observed a decrease in μ FET , for much lower strains in the device (strain range: 0.7–1.25%). This behaviour can be attributed to several factors such as the difference in strain between the layers involved in device fabrication, development of micro-cracks in the dielectric layer and the metal contacts with the crystal.…”
Section: Resultscontrasting
confidence: 54%
“…The paucity of the reported DFT strain–energy data on elastically deformable molecular crystals limits our ability to compare these findings to the uniaxial strain behaviour of other elastically bendable molecular crystals. However, comparable periodic DFT calculations on rhombohedral crystalline GeTe ( r -GeTe) suggests 41 that the minimum in the strain-energy curve need not always be at zero strain, and in the case of r -GeTe it is as high as 2.47% uniaxial strain for its phase 2 structure. For DPP-diMe, the DFT results are in excellent agreement with the results of the experimental mechanical bending tests (see ESI, Fig.…”
Section: Resultsmentioning
confidence: 99%